For $x \in R$,$f(x) = $$\left| {\log 2 - \sin x} \right|$ and $g(x) = f(f(x))$, then:
A. $g$ is not differentiable at $x = 0$
B. $g'(0) = \cos (\log 2)$
C. $g'(0) = - \cos (\log 2)$
D. $g$ is differentiable at $x = 0$and $g'(0) = - \sin (\log 2)$
Answer
Verified
482.4k+ views
Hint:We have the function $f(x),g(x)$.According to the problem given, it is very clear that we need to find the differentiability of $g(x)$ at $x = 0$ and then find the value of $g'(0)$. So firstly we will check whether $g(x)$ is differentiable at $x = 0$ and if it is, then we will find $g'(0)$
Complete step-by-step answer:
$x \in R$,$f(x) = $$\left| {\log 2 - \sin x} \right|$ $ - - - - - (1)$
$g(x) = f(f(x))$$ - - - - - (2)$
It is very clear from the options that we need to find the differentiability of $g(x)$ at $x = 0$
We know that if $g(x)$ is continuous at $x = 0$, when
$g(0) = \mathop {\lim }\limits_{x \to 0} g(x)$
So firstly,
$g(0) = f(f(0))$
Using (1),
$g(0) = \left| {\log 2 - \sin 0} \right|$
As $\sin 0 = 0$, so
$g(0) = f\left| {\log 2} \right|$
$g(0) = \left| {\log 2 - \sin (\log 2)} \right|$$ - - - - - (3)$
Now taking
$\mathop {\lim }\limits_{x \to 0} g(x) = \mathop {\lim }\limits_{x \to 0} f(f(x))$
$ = \mathop {\lim }\limits_{x \to 0} $$f(\left| {\log 2 - \sin x} \right|)$
Using (1),
$ = \mathop {\lim }\limits_{x \to 0} $$\left| {\log 2 - \sin (\log 2)} \right|$
Therefore:
$\mathop {\lim }\limits_{x \to 0} g(x)$$ = \left| {\log 2 - \sin (\log 2)} \right|$$ - - - - - (4)$
Now from (3) and (4)
$g(0) = \mathop {\lim }\limits_{x \to 0} g(x)$
So $g(x)$ is continuous at $x = 0$, hence differentiable also.
Now we will find $g'(0)$
Differentiating (2) and using the chain rule,
$g'(0)$$ = f'(f(x)).f'(x)$
Using $x = 0$
$ = f'(f(0)).f'(0)$
Now differentiating (1) with respect to $x$
$f'(x) = - \cos x - - - - - (6)$
Put $x = 0$ in (1) and (6)
$f(0) = \left| {\log 2} \right|$ and $f'(0) = - \cos 0 = - 1$
Now use (5) by putting these values in it,
$g'(0)$$ = f'(\left| {\log 2} \right|).( - 1) - - - - - (7)$
Now putting $x = \left| {\log 2} \right|$in (6)
$f'(\left| {\log 2} \right|) = - \cos (\left| {\log 2} \right|)$
Now putting this in (7)
$g'(0)$$ = - \cos (\left| {\log 2} \right|).( - 1) = \cos \left( {\left| {\log 2} \right|} \right)$
So, the correct answer is “Option B”.
Note:Here in the last step we have written that $\left| {\log 2} \right| = \log 2$ because $\log 2$ is the positive number.in this question, we have also taken the derivative of $f$ which means that it is differentiable. So in this way we can easily solve the problem.
Complete step-by-step answer:
$x \in R$,$f(x) = $$\left| {\log 2 - \sin x} \right|$ $ - - - - - (1)$
$g(x) = f(f(x))$$ - - - - - (2)$
It is very clear from the options that we need to find the differentiability of $g(x)$ at $x = 0$
We know that if $g(x)$ is continuous at $x = 0$, when
$g(0) = \mathop {\lim }\limits_{x \to 0} g(x)$
So firstly,
$g(0) = f(f(0))$
Using (1),
$g(0) = \left| {\log 2 - \sin 0} \right|$
As $\sin 0 = 0$, so
$g(0) = f\left| {\log 2} \right|$
$g(0) = \left| {\log 2 - \sin (\log 2)} \right|$$ - - - - - (3)$
Now taking
$\mathop {\lim }\limits_{x \to 0} g(x) = \mathop {\lim }\limits_{x \to 0} f(f(x))$
$ = \mathop {\lim }\limits_{x \to 0} $$f(\left| {\log 2 - \sin x} \right|)$
Using (1),
$ = \mathop {\lim }\limits_{x \to 0} $$\left| {\log 2 - \sin (\log 2)} \right|$
Therefore:
$\mathop {\lim }\limits_{x \to 0} g(x)$$ = \left| {\log 2 - \sin (\log 2)} \right|$$ - - - - - (4)$
Now from (3) and (4)
$g(0) = \mathop {\lim }\limits_{x \to 0} g(x)$
So $g(x)$ is continuous at $x = 0$, hence differentiable also.
Now we will find $g'(0)$
Differentiating (2) and using the chain rule,
$g'(0)$$ = f'(f(x)).f'(x)$
Using $x = 0$
$ = f'(f(0)).f'(0)$
Now differentiating (1) with respect to $x$
$f'(x) = - \cos x - - - - - (6)$
Put $x = 0$ in (1) and (6)
$f(0) = \left| {\log 2} \right|$ and $f'(0) = - \cos 0 = - 1$
Now use (5) by putting these values in it,
$g'(0)$$ = f'(\left| {\log 2} \right|).( - 1) - - - - - (7)$
Now putting $x = \left| {\log 2} \right|$in (6)
$f'(\left| {\log 2} \right|) = - \cos (\left| {\log 2} \right|)$
Now putting this in (7)
$g'(0)$$ = - \cos (\left| {\log 2} \right|).( - 1) = \cos \left( {\left| {\log 2} \right|} \right)$
So, the correct answer is “Option B”.
Note:Here in the last step we have written that $\left| {\log 2} \right| = \log 2$ because $\log 2$ is the positive number.in this question, we have also taken the derivative of $f$ which means that it is differentiable. So in this way we can easily solve the problem.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE